Pertanggungjawaban Dealer Kendaraan atas Keterlambatan Penyerahan STNK Kepada Pembeli: Studi Putusan Nomor 23/Pdt.G.S/2022/PN.Mnd - Suci Andara Sari; Salwa Ayu Anggraeni; Kamilia Zulfa Taryono; Vivian Daniella Mapandiy; Sabrina Aulia Paramitha Yunian Putri; Dwi Aryanti Ramadhani (Esensi Hukum, 2025)
This study examines the liability of a vehicle dealer that failed to deliver the Vehicle Registration Certificate (STNK) in a timely manner, as reflected in Decision No. 23/Pdt.G.S/2022/PN.Mnd. The delivery of the STNK forms an essential part of the seller’s performance in a vehicle sales contract, and any delay affects the buyer’s rights and legal certainty. The purpose of this research is to explain the structure of obligations between the parties and to analyze how the court assessed the elements of tort in adjudicating the dispute. This research adopts a normative juridical method using a conceptual approach to the law of obligations and tort, combined with a case approach through the examination of evidence and judicial reasoning within the decision. The findings indicate that the dealer’s delay constitutes negligence that breaches its legal duties, infringes the buyer’s rights, and disregards the principle of due care. The court confirmed a causal connection between the delay and the buyer’s material and immaterial losses, leading to an order requiring the dealer to deliver the STNK, compensate damages, and bear certain financial obligations. These findings highlight the necessity for dealers to comply with administrative responsibilities and reinforce consumer protection in motor vehicle transactions.